Master tracks in different resolutions of METEOR cruise M211, Nice - Ponta Delgada, 2025-06-14 - 2025-07-26 - Wurl, Oliver (Institute for Chemistry and Biology of the Marine Environment, Carl von Ossietzky University Oldenburg, Germany, 2025)
Raw data acquired by position sensors on board RV METEOR during expedition M211 were processed to receive a validated master track which can be used as reference of further expedition data. During M211 the motion reference unit Kongsberg SeaTex AS MRU-5 combined with Kongsberg SeaTex AS Seapath 320 and two SAAB R6 DGPS receiver were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.